Hubungan Sarapan Pagi dengan Status Gizi dan Prestasi Akademik Mahasiswa - Sammeng, Wahyuni; Soumokil, Octovina (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2023)
Breakfast contributes 25% of the total daily nutritional intake. The benefits of breakfast can improve learning achievement. The long-term effects of nutritional intake and status can influence cognitive. This research aimed to determine the relationship between breakfast and the nutritional status and academic achievement of students. This research is an observational analytic with a cross-sectional study approach carried out on nutrition students at the Maluku Ministry of Health Polytechnic. The population was 176 people and the sample was 71 people who were willing to be involved in the research until completion. The research location was carried out at the Maluku Ministry of Health Polytechnic. The dependent variables used are nutritional status and academic achievement, while the independent variable is breakfast. Analysis of the relationship between variables was carried out using a chi-square. The results of the study showed a correlation between breakfast and nutritional status, p-value (0.002) and breakfast with achievement, p-value (0.205). In conclusion, there is a relationship between breakfast and students' nutritional status, but it has no relationship with academic achievement. It is recommended that there be similar research with a diversity of variables that can show factors that influence the nutritional status and academic achievement.